2017
DOI: 10.1186/s12877-017-0490-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low-repetition and light-load power training on bone mineral density in postmenopausal women with sarcopenia: a pilot study

Abstract: BackgroundAge-related reduction in bone mineral density (BMD) is generally accelerated in women after menopause, and could be even more pronounced in individuals with sarcopenia. Light-load power training with a low number of repetitions would increase BMD, significantly reducing bone loss in individuals at risk of osteoporosis. This study investigated the effects of low-repetition, light-load power training on BMD in Japanese postmenopausal women with sarcopenia.MethodsThe training group (n = 7) followed a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 27 publications
2
36
0
1
Order By: Relevance
“…Past work has also examined the osteogenic effect of low‐repetition and light‐load power training on BMD in post‐menopausal women . Here, it was shown that wearing a weighted vest while performing squats, lunges, calf, and toe raises twice a week for 6 weeks leads to significantly greater BMD in the pelvis.…”
Section: Discussionmentioning
confidence: 94%
“…Past work has also examined the osteogenic effect of low‐repetition and light‐load power training on BMD in post‐menopausal women . Here, it was shown that wearing a weighted vest while performing squats, lunges, calf, and toe raises twice a week for 6 weeks leads to significantly greater BMD in the pelvis.…”
Section: Discussionmentioning
confidence: 94%
“…Bone is a dynamic organ that modulates the rate of new bone formation in response to varying levels of mechanical strain. Weight‐bearing exercises have been shown to increase bone density, cortical thickness, and bone strength in the general population . Because lower extremity paralysis is a contributing factor to disuse osteoporosis, reintroduction of mechanical loading may effectively stimulate bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Weight-bearing exercises have been shown to increase bone density, cortical thickness, and bone strength in the general population. (15)(16)(17)(18)(19) Because lower extremity paralysis is a contributing factor to disuse osteoporosis, reintroduction of mechanical loading may effectively stimulate bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Weighted vests have been used as an intervention to improve strength and function in the older adult population (Bean et al 2002;Bean et al 2004;Greendale et al 1993;Greendale et al 2000;Salem et al 2004;Shaw and Snow 1998;Snow et al 2000). Recent research on weighted vest use has investigated its impact on body composition (Normandin et al 2018), bone metabolism (Hamaguchi et al 2017;Klentrou et al 2007;Roghani et al 2013), and lower extremity biomechanics (Mair et al 2014;Puthoff et al 2006). As a versatile intervention, weighted vests may optimize access to exercise modalities, at a low cost, in a home exercise program setting.…”
Section: Introductionmentioning
confidence: 99%
“…Both loads were found to be ineffective at improving measures of strength and function (Greendale et al 2000). In the literature to date, weighted vest dosages have ranged from 0-20% of body weight (Greendale et al 2000;Hamaguchi et al 2017;Salem et al 2004;Shaw and Snow 1998) with no optimal dosage having been established for the use of this intervention in community dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%